Pengabdian Masyarakat Pendidikan Kesehatan Menjaga Kesehatan dan Kebugaran melalui Olahraga bagi Lansia di Posyandu Eka Harapan Kelurahan Pahandut Palangka Raya: Community Service Health Education Maintaining Health and Fitness through Sports for the Elderly at the Eka Harapan Posyandu in Pahandut Palangka Raya Village - Carolina, Putria; Tarigan, Yelstria Ulina; Novita, Bella; Indriani, Desi; Efriadi, Efriadi; Yangan, Enteng Pandi; Mendi, Mendi; Afiana, Marsiane (Jurnal Surya Medika (JSM), 2019)
Elderly is a person experience age growth accompanied by a decrease in physical function characterized by a reduction in muscle mass and strength, a maximum heart rate, an increase in body fat, and a decline in brain function. As you get older, your body will not experience development again, so there is no increase in physical quality. In old age, a person suffers from a particular disease but does not mean that he should not exercise. Exercise is beneficial for physical and spiritual health. The benefits of exercise include promoting blood circulation, strengthening muscles, preventing bone loss, lowering blood pressure, lowering bad cholesterol, and raising good cholesterol. Use is also beneficial for burning calories, improving muscle balance and coordination, and even exercise can boost immunity. While other benefits of exercise are usually able to eliminate constipation, make sleep better, and reduce depression. The method of implementing the activity is to use a health education strategy for the elderly group at Posyandu Lansia Eka Harapan Kelurahan Pahandut Kota Palangka Raya. The event was carried out by providing health education with lecture and question methods. The health education media used are LCD projectors and leaflets distributed to the elderly and carrying out elderly fitness exercises. The material provided is about the importance of maintaining health and fitness through exercise. As long as the activities are running, the environment is conducive, and the elderly are enthusiastic about listening and actively asking when given the opportunity for discussion. The results of the health education evaluation showed that the elderly were able to mention and explain the importance of maintaining health again. Community service activities carried out by lecturers, and students to the elderly can be declared victorious. Through the results of the evaluation during health education took place namely the existence of a positive response from the elderly and also able to mention again about the material that has been presented.